Beyond recognition: Identification and disidentification in visual resistance to stigma - Meriluoto, Taina (The Sociological Review, 2024)
This article theorizes visual practices of stigma resistance as a continuous play with identification and disidentification. Based on an ethnographic study of young, stigmatized activists' self-images, I argue that the oft-employed concept of recognition
Keywords: Multiplicity; Stigma Resistance; Visual Resistance; Ethnographic Study